PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE 7E PADA MATERI PEMANASAN GLOBAL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS VII SMP NEGERI 25 PEKANBARU - Fajrah, Ria Nur; Azhar, Azhar; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the improving of students cognitive learning outcomes by applying the learning cycle 7e model, and to know the difference in students learning outcomes in the class applying the learning cycle 7e method with the class applying conventional method in SMP Negeri 25 Pekanbaru. The type of this research is quasi eksperimental design with nonequivalent kontrol group design. The population in this study is 360 students that spread over in nin classes. The sample was taken by simple random sampling method obtained from 2 classes with 81 students as the study samples. The instrument of data collection in this study uses written questions in the form of multiple choice reasoned with 4 choices as much as 15 questions through pretest and posttest given to the experimental class and control class. Data were analyzed using descriptive and inferential analysis. Descriptive analysis results obtained an average absorption capacity of 78,67% experimental class with good learning category and 43,57% control class with not good category. With the result of the inferential analysis with an independent sample t-test, there are significant differences in learning outcomes between the experimental class and the control class, where the experimental class has a higher increase in learning outcomes. The result of this study provide information that the application of learning cycle 7e models in SMP Negeri 25 Pekanbaru can improve students’ cognitive learning outcomes.Key Words: Learning cycle 7E, cognitive learning outcomes, global warming